2018
DOI: 10.1002/cepa.879
|View full text |Cite
|
Sign up to set email alerts
|

The sustainability of wall solutions: Life Cycle Assessment (LCA) of different solutions for external closures

Abstract: In building's sustainability assessment, the role of the main construction materials is crucial. Even though the number of components is very high, the heaviest environmental impacts are due to a very short list, which comprises structures and envelope. For this reason, good environmental performances of walls materials are the base for achieving high sustainability levels for the building.The Life Cycle Assessment (LCA) is a consolidated scientific method for the analysis of the environmental profile of produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…An assessment of the impacts of external walls is specifically essential in the context of Kazakhstan s extremely harsh climatic conditions, with temperatures ranging from −40 to +35 degrees Celsius. The extended length of cold weather with a district heating period of nearly 8 months starting in October and lasting till May, along with the fact that the significant part of the exiting building stocks are multistory apartment blocks, justified the choice of external walls as it is the building envelope component that is responsible for the central portion of energy loss and material use [15,17,18]. This decision can be supported by findings of the life-cycle energy use assessment studies conducted in regions with cold temperatures, studies which suggested that increasing the insulation of external walls and roofs, for example, can lead to significant savings ranging from 10% to 30% depending on climatic conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An assessment of the impacts of external walls is specifically essential in the context of Kazakhstan s extremely harsh climatic conditions, with temperatures ranging from −40 to +35 degrees Celsius. The extended length of cold weather with a district heating period of nearly 8 months starting in October and lasting till May, along with the fact that the significant part of the exiting building stocks are multistory apartment blocks, justified the choice of external walls as it is the building envelope component that is responsible for the central portion of energy loss and material use [15,17,18]. This decision can be supported by findings of the life-cycle energy use assessment studies conducted in regions with cold temperatures, studies which suggested that increasing the insulation of external walls and roofs, for example, can lead to significant savings ranging from 10% to 30% depending on climatic conditions.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of the significance of stages from a building s life cycle perspective, energy use in regions with cold temperature in operational stage can reach 80%-90%, which is the main merit or simplification, whereas the manufacturing of construction materials and on-site construction and demolition account for 10%-20% and 1%, respectively [6][7][8][9][10]. Hence, for simplification purpose, as well as due to limited amounts of data on the construction materials and the methods of existing building stocks, it was thought to be reasonable to focus on the operational and embodied energy of the buildings [14,15].…”
Section: Life Cycle Assessment (Lca)mentioning
confidence: 99%
“…It was found that aluminum siding has the best performance in terms of sustainability. Another study was carried out by Paleari and Miliani (2018) with the goal of comparing the environmental performance of various building enclosure technologies, with the favorable behavior of AAC blocks being highlighted. For improving common wall structures in Tehran, Iran, a novel optimization approach according to the LCA was proposed by Ramin et al (2017).…”
Section: Introductionmentioning
confidence: 99%
“…Taşıyıcı sistemlerin özellikle incelenmesinin sebebi, strüktürlerin kütlesel ağırlığının binanın tamamına kıyaslandığında oldukça baskın olması ve diğer kalemlere göre en çok enerjiyi tüketen ve en çok karbon salınımına neden olan kısmını oluşturmasıdır. Daha önce yapılan çalışmalarda yapıların belli bölümlerinin farklı malzemeler ile üretilmesi halinde tüketilen enerji ve doğaya salınan karbon miktarları karşılaştırılmıştır [20][21][22]. Bu çalışma ise bir konutun tamamı üzerinde ahşap, betonarme ve çelik yapım sistemlerinin uygulanarak karşılaştırılması bakımından özgündür.…”
Section: Introductionunclassified